ANIMASI INTERAKTIF PEMBELAJARAN PENGENALAN HEWAN DAN ALAT TRANSPORTASI UNTUK SISWA TAMAN KANAK - KANAK - Mahardika, Andaru; Destiana, Henny (LPPM Universitas Nusa Mandiri, 2014)
Learning systems are still using the method of the teacher heard verbal information only now perceived is no longer effective. In need of a better learning system and modern that can help students absorb the material more in-depth study and intact because the method is still widely used and bore the impress saturated, resulting in fewer students understand the lesson. But if enriched with activities see, touch, feel, experience the fun and impress students' understanding through the media better understand the intent of the lesson. Interactive animation is one of the technologies that can be used as a medium of learning, in this case, the introduction of animal learning media and means of transportation for kindergarten students - kindergarten. The software used for interactive learning media animation is Macromedia Flash 8 and Adobe Flash Player.